Printed Nonvolatile Resistive Memories Based on a Hybrid Organic/Inorganic Functional Ink. Issue 8 (8th June 2017) - Casula, Giulia; Tkacz‐Szczesna, Beata; Busby, Yan; Ranoszek‐Soliwoda, Katarzyna; Tomaszewska, Emilia; Celichowski, Grzegorz; Grobelny, Jaroslaw; Pireaux, Jean‐Jacques; Cosseddu, Piero; Bonfiglio, Annalisa
Abstract : Organic memories are increasingly being considered as promising candidates for a number of novel consumer applications, such as smart labels and smart packaging devices. Indeed, organic memories can be fabricated on highly flexible substrates at low temperatures from liquid phase, employing for instance printing techniques. In this work, a nonvolatile resistive memory element conceived for large‐area processing and operation in ambient conditions is presented. In particular, a functional ink made out of an air stable organic semiconductor, namely ActivInk N1400, and gold nanoparticles (NPs) is developed and optimized for the fabrication of high performance memories through inkjet printing. The ink formulation is varied in order to explore the influence of Au NPs concentration on the switching behavior. Devices are operated in ambient conditions with reproducible memory behavior, high ON/OFF current ratios, and low programming voltages. In depth material analysis with time‐of‐flight secondary ion mass spectrometry and X‐ray photoelectron spectroscopy depth profiles are carried out on operated devices to shine a light on resistive switching mechanism and to determine the average gold content and its 3D distribution in stable memories. Abstract : The fabrication of high performance nonvolatile resistive memories through inkjet printing is presented. A functional ink, made out of an organic semiconductor and gold nanoparticles, is formulated for inkjet printing of the resistive layer. Nanoparticles concentration influence on the resistive switching for effective memory application is investigated. Memory devices can be operated in air and show reproducible switching behavior.